Inequality in Mortality in Spain. (29th April 2021) - González, Libertad; Rodríguez‐González, Ana
Abstract: We analyse the evolution of mortality rates in Spain by age and gender between 1990 and 2018. We compare municipalities, ranked by socio‐economic status (SES) and grouped into bins of similar population size, to study changes not only in levels but also in inequality in mortality across the SES spectrum. We document large decreases in mortality rates throughout the period for all age groups, including children, even after 2000, and continuing after the Great Recession. These declines are stronger for boys and men, who had higher mortality rates to begin with. We find that inequality in mortality across municipalities was low among the young by 2018, while it was higher among adult men and older women. Inequality in fact increased over the period for older men. We explore the role of different causes of death and find that this increase in inequality is driven by stronger improvements in cancer‐related mortality among men living in richer areas. These improvements are not found among women, given their increases in mortality due to lung cancer.